The Axiological Potential Of Scientific Knowledge In The Information Age - Броннікова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article is devoted to the study of the problem of the axiological potential of science. For more than 100 years, philosophy has been analyzing this problem, since the proposed solutions are not just different, but sometimes contradictory to each other. This is connected not only with the essence of science, but also with the understanding of values as the basis of culture. Scientific rationality does not arise from scratch, but the foundation of spiritual values already accumulated by society. As you know, society highly values all forms of social consciousness. But the place of science in culture is special, since only science is able to go beyond the scope of each concrete historical type of practice and show new subject areas to people. The aim and task. In society there are constantly changing values. This is also true for science. At the same time, science does not lose its status in culture, since the intellectualization of society is continued. Science teaches man to think, argue, create new. That is why it is necessary to analyze the causes of attempts to depreciate scientific activity and its results in the information society. Research methods. The methodological basis of the study is a set of philosophical and general scientific methods, which provides an analysis of the processes that take place in modern science and determine the directions of its further development. The article also applies systemic and synergistic approaches. Research results. Despite the successes of classical science, at the beginning of the 20th century, they began to accuse science of dehumanization. Obviously, social crises and wars undermine the authority of science. Throughout the 20th century, anti-scientist criticism has existed. At the same time, the image of science is changing to non-classical, and in the second half of the 20th century - to post-non-classical. Attention to the socio-cultural and historical dimensions of scientific knowledge allows us to re-realize the value potential of science. Discussion. In philosophical literature there are conflicting opinions about the value of science - from full exaltation to stating the "end" of science. The arguments of the opponents are interesting and deserve attention. Conclusions. The problem of the value potential of science is relevant not only in connection with the achievements of the scientific and technical sphere, but also with such phenomena as imitation of science and plagiarism. Taking into account the value potential of science contributes to its success and enhances the level of scientific culture in society as a whole.